Evaluasi Kebijakan Perlindungan, Pembinaan Dan Pengembangan Bahasa Jawa Banten Di Kota Serang - Indra Nizar Purnama; Puteri Annisa Firdaus Zamzami; Fikri Habibi (Universitas Serang Raya, 2023)
Problem: Due to the current globalization, regional languages are decreasing and even some regional languages have been declared extinct. One of the endangered languages is Banten Javanese. Regional languages are mother tongues whose existence is very close to the existence of ethnic groups that give birth and use the language, therefore efforts are needed in maintaining regional languages, one of which is public policy. Purpose: The purpose of this study is to evaluate the policy of Serang Mayor Regulation Number 12 of 2014 concerning the Protection, Development and Development of Banten Javanese Language and Literature Methodology: Research Method in this article, using library research is a method of collecting data by understanding and studying theories derived from various kinds of published literature. Research Findings/Results: The results of this study show that based on policy evaluation criteria according to William N Dunn only three criteria have been achieved while the other three criteria have not been achieved optimally. Paper Type: Literature Study